PERAN KEPEMIMPINAN DAN PENGALAMAN KERJA TERHADAP KINERJA ASN DI KEMENTERIAN AGAMA KABUPATEN SITUBONDO DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Anggraini, Yunita Merdiana; Karnadi, Karnadi; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2023)
The purpose of this study is to analyze the effect of the variables Role of Leadership and Work Experience on ASN Performance at the Ministry of Religion of Situbondo Regency with Job Satisfaction as an Intervening Variable by using the Partial Least Square (PLS) structural equation model. The results of the direct effect hypothesis test using the Smart PLS 3.0 application. Leadership has a significant positive effect on job satisfaction (H1 is accepted), work experience has a significant positive effect on job satisfaction (H2 is accepted), leadership has a significant positive effect on ASN performance (H3 is accepted), work experience has a positive but not significant effect on ASN performance (H4 is rejected ), Job satisfaction has a significant positive effect on ASN performance (H5 is accepted), Leadership has a significant positive effect on ASN performance through job satisfaction (H6 is accepted), and work experience has a positive but not significant effect on ASN performance through job satisfaction (H7 is rejected).